2018
DOI: 10.1016/j.amjcard.2017.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Achieving ≥10 METs With a Negative Stress Electrocardiogram to Screen for High-Risk Obstructive Coronary Artery Disease in Patients Referred for Coronary Angiography After Exercise Stress Testing

Abstract: Functional capacity in exercise stress testing is an independent predictor of cardiac events. Routine use of nuclear perfusion imaging increases radiation burden and cost. Our goal was to assess the clinical utility of exercise functional capacity with stress electrocardiogram (ECG) as an adjunct in predicting the presence of high-risk obstructive coronary artery disease (CAD) on diagnostic coronary angiography. We performed a retrospective study of patients who underwent exercise stress testing for the evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(20 reference statements)
0
5
0
Order By: Relevance
“… 43 - 45 When an individual's functional capacity is low compared to predicted values for his or her gender and age group, additional investigation may be necessary. 46 …”
Section: Pre-participation Screeningmentioning
confidence: 99%
“… 43 - 45 When an individual's functional capacity is low compared to predicted values for his or her gender and age group, additional investigation may be necessary. 46 …”
Section: Pre-participation Screeningmentioning
confidence: 99%
“…14 The patient proceeded to angiography based on the discordance between the atypical symptoms and a low-risk exercise stress test (DTS>12) despite the growing evidence that achieving ≥10 METs with a negative stress ECG resulted in 94% sensitivity and 97% negative predictive value in identifying high-risk CAD. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Negative exercise stress tests indicate absence of a condition, while positive tests point to diagnosis of coronary artery disease (CAD) [ 19 , 20 ]. Interestingly, it has been observed that patients with coronary slow flow phenomenon display negative exercise stress electrocardiography that correlates with enhanced left ventricular function, while those with a positive exercise stress test exhibit impaired left ventricular function [ 21 ]. Accordingly, several studies have reported on the link between EFT and CVD risk in response to the treadmill stress test ( Table 1 ).…”
Section: General Overview Of Eft and Its Impact On Cvdsmentioning
confidence: 99%